The Influence of Organizational Culture, Organizational Commitment and Work Environment on Employee Performance at the Research Center Sungei Putih – Rubber Research Center - Pratama, Nugraha; Sitepu, Abdul Rahman (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
This study aims to determine the influence of organizational culture, organizational commitment and work environment on employee performance at the Sungei Putih Research Center-Rubber Research Center, both partially and simultaneously. This study uses a quantitative approach with a sample of 84 employees. The analysis technique used is multiple linear analysis technique. The results of the study showOrganizational culture has a positive and significant effect on employee performance at Sungei Putih Research Center-Rubber Research Center. So if the organizational culture is high or increasing, then performance can increase. Conversely, if the organizational culture is low or decreasing, then performance will decrease. Organizational commitment has a positive and significant effect on employee performance at Sungei Putih Research Center-Rubber Research Center. So if organizational commitment increases, then performance will also increase. Conversely, if organizational commitment is low or decreasing, then performance will decrease. The work environment has a positive and significant effect on employee performance at Sungei Putih Research Center-Rubber Research Center. So if the work environment is high or increasing, then performance can increase. Conversely, if the work environment is low or decreasing, then performance will decrease. Organizational culture, organizational commitment, and work environment have a positive and significant effect on employee performance at Sungei Putih Research Center-Rubber Research Center. So if organizational culture, organizational commitment, and work environment are high or increasing, then performance can increase. Conversely, if organizational culture, organizational commitment, and work environment are low or decreasing, then performance will decrease.